2013
DOI: 10.1007/s12665-013-2549-y
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus release kinetics in a soil amended with biosolids and vermicompost

Abstract: Wastewater biosolids are large potential sources of macronutrients for agriculture, conservation and restoration of soils; there are, however, few studies on phosphorus (P) release in soils amended with biosolids. Biosolids and vermicomposted biosolids were tested in concentrations (5-30 g amendment kg-1 soil) equivalent to 18-100 Mg ha-1. Desorption of P was determined by successive extractions for 65 days. Soil P was low, and biosolid and vermicompost addition released 8 and 6 times more P, respectively, tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 43 publications
1
8
0
Order By: Relevance
“…Phosphorus availability in sludge is strongly influenced by the wastewater treatment (WWT) processes [37]. The addition of some type of liming agent to stabilize sludge may result in lower total P. The addition of lime was reported to increase sludge pH and decrease the solubility of P by the formation of recalcitrant caphosphate minerals [38]. Since more stringent N and P discharge limits have been implemented in wastewater treatment plants (WWTP) in environmentally sensitive areas, total P in sludge is expected to increase from current values [39].…”
Section: Effect Of Lime-stabilized Sludge On Soil Propertiesmentioning
confidence: 99%
“…Phosphorus availability in sludge is strongly influenced by the wastewater treatment (WWT) processes [37]. The addition of some type of liming agent to stabilize sludge may result in lower total P. The addition of lime was reported to increase sludge pH and decrease the solubility of P by the formation of recalcitrant caphosphate minerals [38]. Since more stringent N and P discharge limits have been implemented in wastewater treatment plants (WWTP) in environmentally sensitive areas, total P in sludge is expected to increase from current values [39].…”
Section: Effect Of Lime-stabilized Sludge On Soil Propertiesmentioning
confidence: 99%
“…These results agree with those of Pizzeghello et al (2011) who indicated that long term use of chemical and organic fertilizers saturated sorption capacities of the soils and thus increased the risk of P losses. It became a common practice to add municipal sewage sludge (MSS) (Smith, 1996;Islas-Espinoza et al, 2014), biosolids (Shu et al, 2016) and manure to soils in many countries around the world to supply P, nitrogen and other macro-and micro-nutrients. In many parts of Iran MSS (Raiesi et al, 2015;Rezapour et al, 2012;Jalali and Arfania, 2010) and manures (Jalali and Ostovarzadeh, 2009) is used to supply plants with P and other nutrients.…”
Section: Degree Of P Saturationmentioning
confidence: 99%
“…Similarly, application of potato-processing wastewater to intact sandy loam lysimeters resulted in relatively higher P concentration in leachate than in wastewater, suggesting that additional P was contributed by soil reserves (Zvomuya et al, 2005). Islas-Espinoza et al (2014) tested biosolids and vermicomposted biosolids in different concentrations (5-30 g amendment kg −1 soil). It was observed that soil P was low and biosolid and vermicompost addition released 8 and 6 times more P, respectively, than soil alone.…”
Section: Introductionmentioning
confidence: 99%